PENGARUH CURRENT RATIO, RETURN ON ASSET, DAN DEBT RATIO TERHADAP PREDIKSI FINANCIAL DISTRESS (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2013-2015) - B1031131028, Sufliantini (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
The purpose of this study was to analyze whether the Current Ratio, Return on Asset, and Debt Ratio could simultaneously influence the companyâ€™s financial distress. This research was a quantitative research of Indonesia Stock Exchange in the period of time 2013-2015 from 35 banking companies. The banking companies were selected by using purposive sampling method. The data for hypothesis were analyzed by using multiple linear regressions with SPSS 20. The result showed that Current Ratio and Return on Asset gave negative and significant impacts toward financial distress. Meanwhile, Debt Ratio did not give positive impact but significant towards financial distress. In addition, Current Ratio, Return on Asset, and Debt Ratio were simultaneously influencing financial distress positively and significantly. Â Key Words: Current Ratio, Return On Asset, Debt Ratio, Financial Distress